Obstáculos à inovação para as MPEs brasileiras: existem diferenças entre inovadoras e não inovadoras? - Silva, Luana Naves Ferreira (2022)
The research analyzes the obstacles that affect innovative and non-innovative Brazilian micro and small companies participating in Pintec (Technological Innovation Research), with the objective of comparing the perceived importance of obstacles to the innovative process for each group of companies, in order to identify whether or not there are significant differences between them. Based on the Schumpeterian view of the process, the relevant national bibliography was raised and, based on the systematic methodology of bibliometric analysis, the most relevant and established studies in the international literature within the scope of the subject in question were surveyed. The data come from Pintec and include all triennial editions (from 1998 to 2017), the empirical analysis methods used were descriptive data analysis and exploratory factor analysis. In the empirical part of the study, descriptive analysis is used to compare the types of obstacles faced by innovative and non-innovative MSEs, in order to diagnose the existence of possible differences in relation to the problems perceived by each of these two groups of companies. Finally, the exploratory factor analysis technique is applied so that a quantitative comparison is made between MSEs, medium-sized companies and large, innovative and non-innovative companies The comparative results between MSEs, medium-sized companies and large companies do not capture the existence of a great heterogeneity among Brazilian companies, what was noticed was that there are small differences in perception regarding the importance of obstacles to innovation. Despite this, the results are relevant for understanding what are the obstacles that most significantly impact the innovation process of Brazilian companies.